Nutrient management: as a panacea to improve the caryopsis quality and yield potential of durum wheat (Triticum turgidum L.) under the changing climatic conditions - Melash, Anteneh Agezew; Bogale, Amare Assefa; Bytyqi, Bekir; Nyandi, Muhoja Sylivester; Ábrahám, Éva Babett (Frontiers in Plant Science, 2023)
The increasing human population and the changing climate, which have given rise to frequent drought spells, pose a serious threat to global food security, while identification of high-yielding drought-tolerant genotypes coupled with nutrient management remains a proficient approach to cope with these challenges. An increase in seasonal temperature, recurring drought stress, and elevated atmospheric CO2 are alarmingly affecting durum wheat production, productivity, grain quality, and the human systems it supports. An increase in atmospheric carbon dioxide can improve wheat grain yield in a certain amount, but the right amount of nutrients, water, and other required conditions should be met to realize this benefit. Nutrients including nitrogen, silicon, and sulfur supply could alleviate the adverse effects of abiotic stress by enhancing antioxidant defense and improving nitrogen assimilation, although the effects on plant tolerance to drought stress varied with nitrogen ionic forms. The application of sewage sludge to durum wheat also positively impacts its drought stress tolerance by triggering high accumulation of osmoregulators, improving water retention capacity in the soil, and promoting root growth. These beneficial effect of nutrients contribute to durum wheat ability to withstand and recover from abiotic stress conditions, ultimately enhance its productivity and resilience. While these nutrients can provide benefits when applied in appropriate amounts, their excessive use can lead to adverse environmental consequences. Advanced technologies such as precision nutrient management, unmanned aerial vehicle-based spraying, and anaerobic digestion play significant roles in reducing the negative effects associated with nutrients like sewage sludge, zinc, nanoparticles and silicon fertilizers. Hence, nutrient management practices offer significant potential to enhance the caryopsis quality and yield potential of durum wheat. Through implementing tailored nutrient management strategies, farmers, breeders, and agronomists can contribute to sustainable durum wheat production, ensuring food security and maintaining the economic viability of the crop under the changing climatic conditions.